Quality of Life in Siriraj Hospital’s Patients Undergoing Lumbar Level Fusion for Degenerative Spondylolisthesis: A Retrospective Cohort Study - Siribanchachai, Kamolchanok; Chongthawonsatid, Sukanya; Chotivichit , Areesak (Integrated Social Science Journal, Mahidol University, 2022)
This research employed a retrospective cohort study to identify factors affecting the quality of life among Siriraj Hospital’s 145 patients undergoing lumbar fusion (L4-L5) for degenerative spondylolisthesis. The researchers collected data of these patients from an electronic medical record (EMR) between January 1, 2014 to December 31, 2019 and followed up their quality of life by phone interview until November 30, 2020. The follow-up period ranges from 10 months to 6.8 years. Instruments used in this research included patients’ medical and health records and the Quality of Life questionnaire which consisted of 2 dimensions: the EQ-5D-5L and the Visual Analog Scale (VAS). The findings of this research revealed that patients who had suffered leg pain symptoms before the surgery reported having extremely low quality of life especially in terms of body mobility, usual activities, pain or discomfort, and anxiety or depression compared with patients who had no leg pain symptoms before the surgery. Next, patients who were followed up for 4 years or more after the surgery reported having extremely low quality of life especially in terms of body mobility, self-care, and usual activities compared with patients who were follow-up for less than 2 years and 2 to 4 years after the surgery. A factor affecting patients’ quality of life was a follow-up treatment duration and factors affecting patients’ health status were the disease severity at grade II and surgical complications. Recommendations of this research include doctors should explain medical matters to patients, especially (1) patients will likely have certain complications after the surgery and (2) patients will likely have low quality of life after 4 years of the surgery, especially in terms of body mobility, self-care, and usual activities. Thus, patients should stretch muscles, maintain a healthy weight, and see their doctors regularly after the surgery.